The evolution of electric and hybrid vehicles and their influence on sustainable transport: A review and future research lines - Alberto-Tomas Delso-Vicente; Marisol-Carvajal Camperos; Margarita Almonacid-Durán (Sustainable Technology and Entrepreneurship)
This study presents a systematic review of the academic literature on electric and hybrid vehicles, their ecosystems, and supporting infrastructure over the period 2008–2024. Using the PRISMA methodology, the research evaluates related studies, exploring trends and developments in charging infrastructure, lithium batteries, and the integration of renewable energy, as well as the regulatory and environmental challenges faced by the sector. This work is both novel and significant as it provides a comprehensive and systematic perspective on the most relevant research in the field of electric and hybrid vehicles. Unlike previous studies that often focus on specific aspects, such as life cycle analysis, circular economy, or thermal management of batteries, this review adopts a holistic approach. The analysis of the literature highlights the exponential growth of charging infrastructure and technological progress in lithium batteries, while underscoring persistent challenges related to standardisation and sustainability. The findings suggest the need for policies that foster public-private collaboration, diversify lithium sources, and integrate renewable energy, enabling an equitable transition to sustainable mobility.